1989
DOI: 10.1016/0735-1097(89)90391-4
|View full text |Cite
|
Sign up to set email alerts
|

Regional sympathetic denervation after myocardial infarction in humans detected noninvasively using I-123-metaiodobenzylguanidine

Abstract: Transmural myocardial infarction in dogs produces denervation of sympathetic nerves in viable myocardium apical to the infarct that may be arrhythmogenic. It is unknown whether sympathetic denervation occurs in humans. The purpose of this study was to use iodine-123-metaiodobenzylguanidine (MIBG), a radiolabeled guanethidine analog that is actively taken up by sympathetic nerve terminals, to image noninvasively the cardiac sympathetic nerves in patients with and without ventricular arrhythmias after myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
102
2
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(112 citation statements)
references
References 16 publications
6
102
2
2
Order By: Relevance
“…Functional stress testing results are consistent with the concept that TMR causes sympathetic denervation, masking ischemic symptoms and reducing stress-induced angina without actually improving maximal exercise capacity. The sympathetic innervation defects were significantly larger than the perfusion defects before the intervention, which could be a result of chronic ischemia, 31 previous myocardial infarction, 32 and/or diabetic autonomic neuropathy. 17,33 Whether the extent of sympathetic denervation noted in our study after TMR can alone explain the improvement in angina is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Functional stress testing results are consistent with the concept that TMR causes sympathetic denervation, masking ischemic symptoms and reducing stress-induced angina without actually improving maximal exercise capacity. The sympathetic innervation defects were significantly larger than the perfusion defects before the intervention, which could be a result of chronic ischemia, 31 previous myocardial infarction, 32 and/or diabetic autonomic neuropathy. 17,33 Whether the extent of sympathetic denervation noted in our study after TMR can alone explain the improvement in angina is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings of reduced atrial myocardial blood flow 16 and histological similarities between chronically ischemic ventricular myocardium and atrial myocardium in sustained AF 31 suggest the possibility of ischemia as a trigger. Myocardial infarction causes sympathetic denervation in the ventricle 32 ; however, the effects of long-term ischemia on ventricular sympathetic innervation are unknown. In diabetic cardiac autonomic neuropathy, regional hyperinnervation (increased HED retention) can accompany sympathetic denervation.…”
Section: Autonomic Remodelingmentioning
confidence: 99%
“…26 In addition, heterogeneity of ventricular repolarization because of heterogeneous sympathetic innervation after MI may have a potential arrhythmogenic effect. [27][28][29] A previous study demonstrated that ventricular arrhythmias occurring in patients who had suffered MI were associated with increased mortality during the follow-up period. 30 In a multicenter study, paired VPCs after MI were associated with a more than 3-fold increase in the odds ratio of mortality compared with those with no VPC, and ventricular tachycardia with a 5-to 6-fold increase in the odds ratio.…”
Section: Effect Of Pc On Ventricular Arrhythmiasmentioning
confidence: 99%